2011
DOI: 10.1021/jm200642w
|View full text |Cite
|
Sign up to set email alerts
|

A Small Nonrule of 3 Compatible Fragment Library Provides High Hit Rate of Endothiapepsin Crystal Structures with Various Fragment Chemotypes

Abstract: Druglike molecules are defined by Lipinski's rule of 5, to characterize fragment thresholds, they have been reduced from 5 to 3 (Astex's rule of 3). They are applied to assemble fragment libraries, and providers use them to select fragments for commercial offer. We question whether these rules are too stringent to compose fragment libraries with candidates exhibiting sufficient room for chemical subsequent growing and merging modifications as appropriate functional groups for chemical transformations are requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
137
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(145 citation statements)
references
References 70 publications
0
137
0
5
Order By: Relevance
“…Fragments 15 and 16 explore a higher level of molecular complexity than the initial fragments 5–13 , violate the Ro3, and would have likely failed to pass filters commonly applied to construct current fragment libraries. To this end, a recent study has suggested that alleviating some of these strict criteria can lead to higher hit rates of fragments and still identify suitable starting points for future design (Köster et al, 2011). Both 15 and 16 contain an aromatic ring attached to an amino acid moiety.…”
Section: Discussionmentioning
confidence: 99%
“…Fragments 15 and 16 explore a higher level of molecular complexity than the initial fragments 5–13 , violate the Ro3, and would have likely failed to pass filters commonly applied to construct current fragment libraries. To this end, a recent study has suggested that alleviating some of these strict criteria can lead to higher hit rates of fragments and still identify suitable starting points for future design (Köster et al, 2011). Both 15 and 16 contain an aromatic ring attached to an amino acid moiety.…”
Section: Discussionmentioning
confidence: 99%
“…The value of using the RO3 in FBDD is being (correctly) challenged 4 as many useful fragment hits do not adhere to its restrictions (see the Practical Fragments blog website). We have always believed that the RO3 concept has limitations and, like other rules related to desirable physicochemical properties, such as the 'rule of five' guidelines 5 , it is simply a guideline that should not be overemphasized.…”
Section: Rule Of Threementioning
confidence: 99%
“…We circumvent this issue by using ligand fragments resembling a “full substructure set.” Similar to Lipinski's “rule of five” [51] that describes small molecule properties correlated with oral bioavailability, there is a “rule of three” for fragments [52]; fragment hits identified through fragment screening tend to satisfy molecular weight <300 Daltons, the number of hydrogen bond donors is ≤3, the number of hydrogen bond acceptors is ≤3, and ClogP is ≤3. However, many successful fragments violate the “rule of three” [53]. Additionally, fragments in the “rule of three” refer to compounds at least 120 Daltons in molecule weight, which is larger than the fragments in FragFEATURE's knowledge base.…”
Section: Discussionmentioning
confidence: 99%